Employee voice in enterprise bargaining: what managers miss when they fail to listen. (1st October 2016) - Townsend, Keith; Loudoun, Rebecca
ABSTRACT: Despite being reregulated several times, the Australian system of 'enterprise bargaining' has remained adversarial in nature and thus has failed to live up to the potential promised. This article examines a case study where employees hold a great deal of power through a strong union. Additionally and separate from the institutional arrangements, employees identify a number of ways that they identify currently affect productivity in their workplace(s), but poorly integrated employee voice systems and a low level of trust means that the benefits of bargaining are somewhat limited. Evidence from this case study suggests that improved trust and a process of listening to, and learning from employee voice are required for employers and employees to better capitalise on bargaining opportunities and shift from distributive bargaining to integrative bargaining models.